اعتراضات العلماء على قبول القياس كدليل شرعي: نظرة أصولية تحليلية = Scholars’ objections on reasoning analogy (al-qiyas) as proof of Islamic law: an analytical jurisprudential study - Mochammad Sahid, Mualimin; Fettane, Amar; Mohamad Zain, Lutfi; Haque, Mesbahul (2018)
The nusus (legal texts) in Syariah (Islamic law) are limited, while issues are endless and keep on changing. There is a need to know hukm (judgment) for every issue so that it does not leave issues without clear judgment. In order to achieve this, scholars sought and discussed a legitimate dalil (proof) to avoid the awkwardness and hardship in practicing religion. The dalil that the scholars have spoken about and differed in terms of its ligitimacy is Al-Qiyas (reasoning analogy). This study aims to clarify the dispute among scholars of usul al-fiqh on issues related to dalil al-Qiyas in which many of them accepted it as dalil syar’ie while others denied it ligitimacy. The study used library research and analytical approach to discuss the issue on how scholars differed in their views and to reveal their evidences and reasons. The study concluded that the scholars differed in their opinios on the issue of Al-Qiyas and its ligitimacy as dalil syar’ie. Those who denied it argued that there is no dalil (proof) of the rule of Allah except Al-Qur’an, As-Sunnah and Ijma’ (the consensus of scholars). As for scholars who considered al-Qiyas as dalil syar’ie, they viewed that in case there is no specific dalil (proof), al-Qiyas (reasoning analogy) is refered to in building of ahkam (judgments) based on the similarity of their illat (reaons), while those who reject it they viewed that all things are primarily considered mubah (permissible).